The birth of nomos - Zartaloudis, Thanos (Encounters in law and philosophy., 2019)
This is a highly original, interdisciplinary study of the archaic Greek word nomos and its family of words. Includes extracts from ancient sources, in both the original and English translation, to give us a new and complete understanding of nomos and its foundational place in the Western legal tradition.